2009
DOI: 10.1007/s11864-008-0079-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lymphocytic Leukemia: New Concepts and Emerging Therapies

Abstract: Remarkable progress in elucidating the biology of chronic lymphocytic leukemia (CLL) has been made over the last two decades. Improved understanding of CLL has lead to new prognostic tools and therapeutic options, and holds promise for eventually finding a cure for this disease. Challenges lie in incorporating the various treatment modalities, including chemotherapy, monoclonal antibodies, immunotherapeutic strategies and novel small molecules, into a comprehensive treatment strategy guided by the biological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…To compare their biological properties and deduce SAR correlations, the compounds were tested for antioxidant activity using ferric ion reducing FRAP and DPPH free radical scavenging tests. Anticarcinogenic potential was evaluated by measuring induction of cytoprotective Keap1‐Nrf2 signalling,16 and cytostatic potential in human leukemia cells 17. The combined approach identified 2‐styrylchromone 3k and chromanone 3r as promising novel benzopyran‐4‐one derivatives, which are now available for further investigation of the mechanisms underlying their biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…To compare their biological properties and deduce SAR correlations, the compounds were tested for antioxidant activity using ferric ion reducing FRAP and DPPH free radical scavenging tests. Anticarcinogenic potential was evaluated by measuring induction of cytoprotective Keap1‐Nrf2 signalling,16 and cytostatic potential in human leukemia cells 17. The combined approach identified 2‐styrylchromone 3k and chromanone 3r as promising novel benzopyran‐4‐one derivatives, which are now available for further investigation of the mechanisms underlying their biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Although PL and lymphoma both had CD5 + B-cell proliferation, the Syk mRNA expression in the tumor samples was significantly decreased compared with that of the PL samples. For neoplastic lymphocytes in CLL the anti-apoptosis effect is enhanced by Syk activation, in spite of reduced Syk mRNA expression [1,2,15]. Therefore, it is considered that activation of SFK and/or suppression of phosphatases promotes or maintains Syk activation.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic lymphocytic leukemia (CLL), expression of Syk mRNA was found to be reduced in one study, but Syk was reported to be activated in another one, and also to work as an inhibitor of apoptosis [1,2,15]. On the other hand, Syk mRNA overexpression was detected in anaplastic lymphomakinase (ALK)-positive cells of anaplastic large cell lymphoma [28].…”
mentioning
confidence: 99%
“…In addition, the use of monoclonal antibodies such as rituximab and alemtuzumab has added substantial benefit when combined with chemotherapy. 1,2 However, the ability to eradicate disease at a molecular level, and improve clinically relevant patient outcome measures, continue to pose difficult challenges. Regardless of the stage of the disease, most patients will relapse after initial treatment and become refractory to salvage chemotherapy with median overall survival ranging from 10 to 19 months.…”
mentioning
confidence: 99%